2017
DOI: 10.1021/acsami.7b12295
|View full text |Cite
|
Sign up to set email alerts
|

Methanol/Oxygen Enzymatic Biofuel Cell Using Laccase and NAD+-Dependent Dehydrogenase Cascades as Biocatalysts on Carbon Nanodots Electrodes

Abstract: The efficient immobilization of enzymes on favorable supporting materials to design enzyme electrodes endowed with specific catalysis performances such as deep oxidation of biofuels, and direct electron transfer (DET)-type bioelectrocatalysis is highly desired for fabricating enzymatic biofuel cells (BFCs). In this study, carbon nanodots (CNDs) have been used as the immobilizing matrixes and electron relays of enzymes to construct (NAD)-dependent dehydrogenase cascades-based bioanode for the deep oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 70 publications
0
28
0
1
Order By: Relevance
“…Examination of values of P max greater than 1 mW cm -2 ( Table 1) indicates that the majority of high-power-density EFCs are based on carbon nanomaterials (CNMs)-based electrodes. CNMs including buckypaper 46,117,303 , carbon felt 74 , carbon cloth, carbon black 16 , CNTs 62,72,[303][304][305][306][307][308][309][310][311][312][313] , carbon fiber 65,273,[314][315][316][317][318] , graphene 73,93,255,319 , porous carbon 11,63,66,320,321 , carbon nanodots 322 , and their combinations thereof 15,35,185,[323][324][325][326][327] have been widely used for the preparation of bioelectrodes. Although allowing significantly improved current densities, two main challenges of using CNMs based high-surface-area electrodes need to be addressed.…”
Section: Employment Of Nanomaterialsmentioning
confidence: 99%
“…Examination of values of P max greater than 1 mW cm -2 ( Table 1) indicates that the majority of high-power-density EFCs are based on carbon nanomaterials (CNMs)-based electrodes. CNMs including buckypaper 46,117,303 , carbon felt 74 , carbon cloth, carbon black 16 , CNTs 62,72,[303][304][305][306][307][308][309][310][311][312][313] , carbon fiber 65,273,[314][315][316][317][318] , graphene 73,93,255,319 , porous carbon 11,63,66,320,321 , carbon nanodots 322 , and their combinations thereof 15,35,185,[323][324][325][326][327] have been widely used for the preparation of bioelectrodes. Although allowing significantly improved current densities, two main challenges of using CNMs based high-surface-area electrodes need to be addressed.…”
Section: Employment Of Nanomaterialsmentioning
confidence: 99%
“…CNDs were prepared according to previous reports [18] [25] [26]. Figure 1 shows the low magnification SEM (Figure 1(A)) and high magnification TEM (Figure 1(B)) images of the obtained CND.…”
Section: Typical Sem and Tem Images Of Carbon Nanodotsmentioning
confidence: 99%
“…In this study, by using GDH-polyMG-CNDs composites as the bioelectrocatalysts for the catalytic electrooxidation of glucose at the bioanode and laccase-CNDs composites as the direct bioelectrocatalyst for oxygen reduction at the biocathode, a membrane-less glucose/air BFC was successfully constructed. The investigations on the direct electron transfer (DET) of blue-copper oxidases including bilirubin oxidase and laccase on CNDs have been studied in our previous studies [18] [26]. These studies have demonstrated that CNDs can efficiently facilitate the DET behaviours of bilirubin oxidase and laccase, and also retain their bioactivity for bio-catalyzing oxygen reduction.…”
Section: Real Applications Of the Fabricated Gdh-polymg-cnds/gc Electmentioning
confidence: 99%
See 2 more Smart Citations